Sex-differences in symptoms and functioning in >5000 cancer survivors: Results from the PROFILES registry. (October 2021) - Oertelt-Prigione, Sabine; de Rooij, Belle H.; Mols, Floortje; Oerlemans, Simone; Husson, Olga; Schoormans, Dounya; Haanen, John B.; van de Poll-Franse, Lonneke V.
Abstract: Background: Previous reports highlight the greater number of side effects that women experience during cancer treatment, but little is known about sex differences in symptoms and functioning in long-term survivors. Methods: We investigated sex differences in the prevalence of physical (EORTC QLQ-C30) and emotional symptoms (Hospital Anxiety and Depression Scale) and loss of functioning (EORTC QLQ-C30) in 5339 cancer survivors (55% males). General linear models were computed to assess the differences in symptoms and functioning between female and male cancer survivors and between survivors and an age-matched reference population. Results: The direct comparison between female and male cancer survivors identified more symptoms, such as nausea and vomiting (M = 5.0 versus. 3.2), insomnia (M = 26.1 versus. 15.9), anxiety (M = 5.2 versus. 4.2), and lower physical (M = 77.5 versus. 82.5) and emotional functioning (M = 83.4 versus. 86.3), in female survivors. However, comparison with an age-matched reference population demonstrated that several symptoms, such as fatigue, dyspnea, anxiety and depression, appeared to be more frequent in male patients. The investigation of functioning domains — compared with a reference population — highlighted further sex-specific differences. Female survivors experienced a moderate net loss in physical and cognitive functioning (−6.1 [95% CI = −8.1; −4, 1] and −5.2 respectively [95% CI = −7; −3.5]), whereas male survivors displayed a significant net loss in role and social functioning compared to the reference population (−9.9 [95% CI = −11.2; −8.6] and −7.7 [95% CI = −9.6; −7.6] respectively). Conclusion: To adequately capture sex differences in symptoms and functioning in long-term cancer survivors, a comparison with a reference population should always be considered. In our study population, this adjustment highlighted a significant and unexpected long-term impact on male patients. Role and social functioning were especially impacted in male patients, emphasizing the need to further investigate these gendered domains. Highlights: Long-term cancer survivors report sex-specific symptoms and functional impairments. Comparison with age-and sex-matched reference group showed more impairment in males. Loss of role and social functioning in males could represent a loss of gender role.